IMPLEMENTASI BAHAN AJAR MEMBACA BERBASIS MASALAH UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS DAN PEMECAHAN MASALAH SISWA KELAS VIII SMPN 25 MALANG - Muhammad Yasin; Endah Tri Priyatni; Suyono Suyono (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
The objective of this study is to see effectiveness of problem based reading materials to improve critical thinking skills, problem solving skills, and learning outcomes. The study used experimental study of One-Group Pretest-Posttest design assigning 25 students of VIII graders of SMPN 25 Malang as sample. Data were collected using observation, test, and questionnaire. The study revealed that (1) students ability of critical thinking improved after implementation of problem solving skills, as indicated by n-gain score in positive manner with average 0.7 in high criteria; (2) students problem solving skills improved seen in n-gain score with positive value and average 0.4 based upon enough criteria; (3) student improvement seen by the classical completeness improved up to 100%.